Epidural Brain Metastases in a Patient with Early Onset Pancreatic Cancer: A Case Report and Literature Review - Aibek E. Mirrakhimov; Farah N. Khan (Case Reports in Oncological Medicine)
We present a case of early onset pancreatic cancer related extra-axial brain metastases. A 46-year-old Caucasian non-Jewish nonobese male with a history of PC diagnosed 3 months ago with metastases to the liver, omentum, malignant ascites, and a history of a pulmonary embolism was admitted to the hospital because of a new onset headache, nausea, and vomiting which started 2 days prior to the encounter. Brain MRI was ordered, which showed acute bihemispheric subdural hematomas and left hemispheric extra-axial heterogeneously enhancing lesions consisting with metastatic disease. The patient was started on ondansentron, metoclopramide, and dexamethasone. The cranial irradiation was started, and the patient’s headache and nausea significantly improved. There are only 9 published reports of extra-axial brain metastases related to the pancreatic cancer, whereas our paper is the first such case reported on a patient with epidural metastases and early onset pancreatic cancer.